Learner Support Gaps in Distance Learning: The Case of Institute for Distance Education and e-Learning, University of Education, Winneba - Dampson, Dandy George; Owusu-Mensah, Francis; Apau, Stephen Kwakye; Osei-Owusu, Benedict (Advances in Social Sciences Research Journal, 2019)
The purpose of the study was to measure the extent to which the learner support needs of distance education learners in the Institute of Distance Education and e-Learning (IDeL) in the University of Education, Winneba were met. The explanatory sequential design under the mixed method approach was adopted. The study sampled 623 students randomly to respond to a questionnaire adapted from Ozoglu (2009). A qualitative data was (subsequently) collected through a focus group discussion with 18 (eighteen) students and an interview with the Registrar of IDeL. The interview data was analyzed thematically. Descriptive and inferential statistics were used for the quantitative data. The study revealed that the support needs of the learners were largely unmet. A need gap analysis revealed a huge difference in terms of e-learning portals, educational software produced by IDeL, communication with course instructors, face- to face academic counseling (tutoring), counselling services to promote students’ self-confidence and help with the admission/registration process. The study further revealed that though sex, age and certificate enrolled for all might predict distance leaners’ support needs, it was age that was statistically significant. This study, therefore, recommends that IDeL expand its support services to match the specific needs of the learners.